The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1063/1.5048982
|View full text |Cite
|
Sign up to set email alerts
|

Boltzmann equation studies on electron swarm parameters in Townsend breakdown of copper vapor plasma using independently assessed electron-collision cross sections

Abstract: Electron transport coefficients in copper vapor plasma are calculated both by two-term expansion of electron Boltzmann equation Bolsig+ and tracking the random motion of electrons using Monte Carlo collision code METHES based upon recently evaluated cross section sets. The copper atoms are evaporated from hot electrode during the post-arc phase of vacuum circuit breakers, in which Townsend breakdown between electrode gaps is probable. The electron energy probability function, electron mean energy, flux/transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Since the average kinetic energy of the ectons ejected from the emitting area is a few electronvolts 38 and they are accelerated by the electric field in the sheath up to several electronvolts, inelastic collisions are dominant in the non-collapsing ion sheath, ultimately producing a Townsend breakdown. We note that Yang et al 39 investigated copper vapor plasma via simulation and reported minimum breakdown voltages of 106–122 V at . Considering that (i) the electron-impact ionization cross section of aluminum is ten times larger than those of copper and argon 40 , 41 , and (ii) the aluminum density is assumed as (few hundred millitorr of vapor pressure), breakdown is initiated within a sub-millimeter region in the non-collapsing sheath where the voltage difference between the background plasma and AIP tip is a few hundred volts.…”
Section: Resultsmentioning
confidence: 81%
“…Since the average kinetic energy of the ectons ejected from the emitting area is a few electronvolts 38 and they are accelerated by the electric field in the sheath up to several electronvolts, inelastic collisions are dominant in the non-collapsing ion sheath, ultimately producing a Townsend breakdown. We note that Yang et al 39 investigated copper vapor plasma via simulation and reported minimum breakdown voltages of 106–122 V at . Considering that (i) the electron-impact ionization cross section of aluminum is ten times larger than those of copper and argon 40 , 41 , and (ii) the aluminum density is assumed as (few hundred millitorr of vapor pressure), breakdown is initiated within a sub-millimeter region in the non-collapsing sheath where the voltage difference between the background plasma and AIP tip is a few hundred volts.…”
Section: Resultsmentioning
confidence: 81%
“…. Researches [51,52] suggest, that background VDF becomes important in the case of small fields. The latter can be taken into account by changing u 0 term in (8): u 0 → u 0 + v bg , where v bg corresponds to thermal velocity, sampled from the background VDF.…”
Section: Evdfsmentioning
confidence: 99%
“…The left panel shows the elastic momentum transfer (1), total ionization (2), and quantities that are obtained by multiplying the total cross section for superelastic collisions with the corresponding fractional populations of the first excited metastable state at indium vapour temperatures of 1260 K, 3260 K, and 5260 K. The left panel also includes the following discrete inelastic transitions: (5s 2 5p) 2 P 3/2 (3), (5s 2 6s) 2 S 1/2 (4), (5s 2 6p) 2 P 1/2 (5), (5s 2 6p) 2 P 3/2 (6), (5s 2 5d) 2 D 3/2 (7), (5s 2 5d) 2 D 5/2 (8), (5s 2 4p) 2 P 1/2 (9), (5s 2 4p) 2 P 3/2 (10), (5s 2 7s) 2 S 1/2 (11) and (5s 2 4p) 2 P 5/2 (12). The right panel includes the following discrete inelastic transitions: (5s 2 7s) 2 P 1/2 (13), (5s 2 7s) 2 P 3/2 (14), (5p 2 6d) 2 D 3/2 (15), (5p 2 6d) 2 D 5/2 (16), (5p 2 4 f ) 2 F 7/2 (17), (5p 2 4 f ) 2 F 5/2 (18), (5p 2 8s) 2 S 1/2 (19), (5p 2 8s) 2 P 1/2 (20), (5s 2 7d) 2 D 3/2 (21), (5s 2 7d) 2 D 5/2 (22) and (5s 2 8p) 2 P 3/2 (23). Integral cross sections for electron scattering in indium vapour for atoms in the metastable state (5s 2 5p) 2 P 3/2 .…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…The primary driving force behind these early studies was the modelling and optimization of light sources containing mercury [8,14,15], sodium [16,17], and zinc [18,19]. Other applications include the modelling of a gas laser [20], the magnetohydrodynamics of arcs [21], and a post-arc breakdown plasma [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation